2022
DOI: 10.1371/journal.pone.0265672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of low vitamin D levels in patients with Hidradenitis suppurativa in Jordan: A comparative cross-sectional study

Abstract: Hidradenitis suppurativa (HS) is a chronic inflammatory disease of the apocrine gland bearing skin, presenting various stages of flexural skin pain, erythema, painful nodules, abscesses, sinuses, and fistulas. We aimed to assess serum vitamin D levels in patients with (HS) in Jordan. a cross-sectional comparative study conducted among 110 patients with HS and 110 matched controls, who didn’t previously receive vitamin D therapy. Serum vitamin D was measured and classified into normal (>30 ng/ml), insufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
4
10
1
Order By: Relevance
“…Research has demonstrated its critical role in epidermis repair and maintenance through its involvement in cell differentiation, proliferation and immune function 17,18 . Our results are consistent with those of Seetan et al (2022), who discovered that vitamin D is effective in treatment of hyperpigmentation disorders 19 . In contrast to the research which observed negligible effects on wound healing, our research suggested that vitamin D plays more prominent role in this regard 20 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Research has demonstrated its critical role in epidermis repair and maintenance through its involvement in cell differentiation, proliferation and immune function 17,18 . Our results are consistent with those of Seetan et al (2022), who discovered that vitamin D is effective in treatment of hyperpigmentation disorders 19 . In contrast to the research which observed negligible effects on wound healing, our research suggested that vitamin D plays more prominent role in this regard 20 …”
Section: Discussionsupporting
confidence: 91%
“…17,18 Our results are consistent with those of Seetan et al (2022), who discovered that vitamin D is effective in treatment of hyperpigmentation disorders. 19 In contrast to the research which observed negligible effects on wound healing, our research suggested that vitamin D plays more prominent role in this regard. 20 The Vitamin D group exhibited the notable decrease in chloasma severity scores, which implied that vitamin D may have therapeutic potential in treatment of pigmentary disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with HS were associated with vitamin D deficiency, which is consistent with the results of other studies 50,51 . A previous study reported that patients with HS are more likely to be vitamin D deficient than patients without HS 50 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, patients with HS have been shown to have low vitamin D levels, which seems to be correlated with disease severity [ 39 , 40 , 41 ]. By controlling proliferation and differentiation of epidermis and its structures (hair follicle in particular), vitamin D is able to regulate skin homeostasis [ 42 ].…”
Section: Gut Microbiome In Hsmentioning
confidence: 99%